Poa trivialis: physiological and pathological components of summer decline, and cultural, selective, and non-selective control methods - Thompson, Cole S. (Kansas State University, 2014)
Rough bluegrass (RBG, Poa trivialis L.) is a difficult-to-control weed that commonly infests cool-season turfgrass swards after movement of vegetative propagules or contamination from seed lots. Rough bluegrass is less tolerant of heat stress than desirable cool-season species such as tall fescue (TF, Festuca arundinacea Schreb. Syn [italicize]Schedonorus [italicize]arundinaceus Schreb.), and often declines during mid-summer due to biotic or abiotic stresses. The objectives of these 2011-2013 controlled environment and field experiments were to: 1) observe growth and physiological differences between ‘Laser’ and ‘Pulsar’ RBG and TF; 2) differentiate between physiological and pathological contributors to RBG decline; 3) determine the effects of TF seeding rate and mowing height on TF/RBG establishment when RBG is a seed contaminant; 4) evaluate herbicide combinations for selective RBG control; and 5) evaluate seasonal timing of glyphosate for nonselective RBG control. Tall fescue was less affected by elevated temperature than RBG. At 35°C, Laser and Pulsar experienced similar reductions in quality, gross photosynthesis (Pg), shoot and root biomass, and root length density compared to when grown at 23°C, but maximum electrolyte leakage was greater for Pulsar (63%) than for Laser (49%). Cell membrane thermostability could contribute to the better heat tolerance of Laser RBG. Evaluation of RBG foliage and roots did not reveal a fungal pathogen associated with RBG decline. Still, repeated applications of azoxystrobin (610 g a.i. ha⁻¹) or pyraclostrobin (556 g a.i. ha⁻¹) increased RBG quality, cover, and Pg during summer compared to untreated RBG, possibly due to poorly understood non-target physiological effects of the fungicides. Mowing TF at 7.6 or 11.4 cm reduced RBG incidence up to 57% compared to mowing at 3.8 cm. Tall fescue seeding rate had no effect on RBG incidence. Several herbicides and herbicide combinations resulted in some RBG injury in the field, but bispyribac-sodium was the only treatment that provided RBG control (16 to 92%) in Manhattan, KS; Hutchinson, KS; and Mead, NE. Spring-applied glyphosate resulted in the lowest RBG coverage (1 to 31%) among field studies in Manhattan and Mead, followed by late-summer applications (6 to 58%), and mid-summer applications (9 to 86%).
Keywords: Poa trivialis; Rough bluegrass; Turfgrass management; Horticulture (0471); Plant Pathology (0480); Plant Sciences (0479)